THE USE OF INNOVATIVE UAVS AND SLAM-LIDAR TECHNOLOGIES FOR MONITORING AT NUCLEAR POWER PLANTS - Semiriakov, Oleksandr (Global Prosperity, 2026)
Abstract. The article is devoted to the analysis of the current state, practical possibilities and prospects of using unmanned aerial vehicles in combination with SLAM and LiDAR technologies for monitoring nuclear power facilities. The purpose of the article is a comprehensive analysis of the current state and prospects of using unmanned aerial vehicles in combination with SLAM and LiDAR technologies for monitoring nuclear power facilities. The work uses methods of analytical review of scientific and industry sources, comparative analysis of technological solutions, generalization of statistical data, systematization of practical cases, as well as logical and structural analysis of trends in the development of unmanned and navigation technologies. The results shows for the first time that the combination of unmanned aerial vehicles with SLAM and LiDAR technologies allows to significantly improve the monitoring of nuclear power facilities by ensuring accurate spatial localization, construction of metrically correct three-dimensional models and stable navigation in conditions of complex geometry, limited lighting and lack of satellite navigation signals. In particular, the integration of active laser sensing with algorithms of simultaneous localization and mapping creates the prerequisites for the transition from fragmentary visual inspections to systematic, reproducible and quantitatively controlled spatial analysis of the state of technological premises and structures. Future directions of technology development are also shown and systematized, in particular, increasing the autonomy of platforms, intellectualization of data processing, integration of multi-sensor complexes and the transition to distributed robotic systems. In practical terms, this creates the prerequisites for active technology transfer to the nuclear energy industry, when companies will be able not only to adapt ready-made solutions, but also to form their own specialized products for inspection, post-accident monitoring and digital modeling of facilities. Thus, the work forms a conceptual basis for combining scientific developments, market trends and applied needs of nuclear infrastructure.